2003
DOI: 10.1038/sj.mp.4001296
|View full text |Cite
|
Sign up to set email alerts
|

Genetic association of acyl-coenzyme A: cholesterol acyltransferase with cerebrospinal fluid cholesterol levels, brain amyloid load, and risk for Alzheimer's disease

Abstract: A common polymorphism of the gene encoding acylcoenzyme A: cholesterol acyltransferase 1 (SOAT1), which is involved in the regulation of b-amyloid peptide generation, is associated with low brain amyloid load (P ¼ 0.03) and with low cerebrospinal fluid levels of cholesterol (P ¼ 0.005). This polymorphism of SOAT1 is also associated with reduced risk for Alzheimer's disease in ethnically distinct populations (P ¼ 0.0001, odds ratio: 0.6, 95% confidence interval 0.4-0.8).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
48
2
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 18 publications
1
48
2
2
Order By: Relevance
“…ABCG1 is one of several genes upregulated by synthetic LXR agonists and is highly expressed in brain. Genetic studies suggest a possible role for ABCG1 in Ab metabolism, as different single nucleotide polymorphism haplotypes show either an increased or decreased odds ratio for AD risk in two European populations (80). Support for a potential role for ABCG1 in APP processing was recently provided by Tansley et al (52), who observed that ABCG1 overexpression increased Ab production 30% and increased APP processing through a-and b-secretase in HEK-APP cells.…”
Section: Discussionmentioning
confidence: 92%
“…ABCG1 is one of several genes upregulated by synthetic LXR agonists and is highly expressed in brain. Genetic studies suggest a possible role for ABCG1 in Ab metabolism, as different single nucleotide polymorphism haplotypes show either an increased or decreased odds ratio for AD risk in two European populations (80). Support for a potential role for ABCG1 in APP processing was recently provided by Tansley et al (52), who observed that ABCG1 overexpression increased Ab production 30% and increased APP processing through a-and b-secretase in HEK-APP cells.…”
Section: Discussionmentioning
confidence: 92%
“…Finally, use of biologically relevant, quantitative phenotypes have been proposed as a means to overcome potential clinical heterogeneity, as such quantitative traits may a) be a less heterogeneous and more direct correlate for the genetic variation(s); b) be less prone to the imprecisions of a clinical phenotype; c) be amenable to inclusion of subjects with pre-clinical disease; and d) allow for downstream functional testing of putative susceptibility variants [ 158,160,163 ]. More recently, the use of quantitative traits such as Aβ levels, mini-mental state examination scores, CSF tau levels, age-at-onset, pathological disease burden and CSF cholesterol levels [ [164][165][166][167][168] have emerged as novel approaches to study candidate AD genes.…”
Section: Candidate Gene Studiesmentioning
confidence: 99%
“…87 A polymorphism in the ACAT gene (the A/A genotype of rs1044925) that results in low brain cholesterol content has been associated with low brain amyloid load and a reduced risk for AD in European populations. 88 ACAT inhibitors have been widely studied for the treatment of atherosclerosis, and may prove equally important for the treatment and prevention of AD. However, the exact mechanism by which CE levels modulate the generation of Ab is not known.…”
mentioning
confidence: 99%